On the Deactivation Analysis of IM-5 Zeolite in Pseudocumene Methylation with Methanol - Shumin Hao; Yongrui Wang; Enhui Xing; Xuhong Mu (Crystals)
In the methylation of pseudocumene with methanol over IM-5 zeolite, the yield of durene can be enhanced. However, poorer stability of the catalytic activity was observed, especially at a higher methanol/pseudocumene ratio. In this paper, conventional characterization methods (XRD, XRF, TGA, SEM, physical adsorption, OH-IR, NH3-TPD, and Py-IR) were used to characterize fresh and deactivated IM-5 zeolite and ZSM-5. FT-IR, XPS, TG-MS, GC-MS, FT-ICR MS, and NMR were employed to characterize deactivated IM-5 zeolite. It was found that the deactivation of IM-5 zeolite was mainly due to the severe coverage of acidic sites and pore channels by carbon deposits. The carbon deposits within the internal surface had a higher abundance, mainly in the form of linear unsaturated chain-like structures with a high degree of unsaturation. The carbon deposits on the external surface were mainly polycyclic aromatic hydrocarbons with alkyl side chains and a high degree of saturation, accompanied by unreacted methanol. Moreover, graphitized carbon existed on both the internal and external surfaces, which made the conventional coke-burning regeneration method unable to restore the activity of the post-reaction IM-5 zeolite. This work had certain reference significance for modulating the acidity and pore channels of zeolite catalysts, thus improving the activity and stability of the catalysts and extending their service life.